Intermediate, Local and Glocal Innovation Models for MNCs Targeting Emerging Markets: The Case of a European Telco Operator in Africa and the Middle East - Ben Mahmoud-Jouini, Sihem; Charue-Duboc, Florence; Hadengue, Marine (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2020)
In this article, we highlight an alternate model of innovation for multinational corporations from advanced markets targeting emerging markets. This model, labeled the intermediate model, is characterized by the nature of the targeted markets as well as the development process. We show that, conversely to the glocal and local models, the intermediate model mixes corporate and local resources from the early stage of the innovation process, during the development and, until the deployment and commercialization of the innovation in the successive emerging markets. We address these questions through the case of a French telco operator targeting Africa and the Middle East.